Discussion of Published Corporate Accounting Data and Stock Prices - Parker, C. Reed (Journal of Accounting Research, 1967)
As a practicing investment analyst, I confess at once that my work is as much intuitive as empirical. Accordingly, my thoughts about Professor Benston's paper do, I fear, slip into intuition more often than they should. However, they are based on my daily experience of gathering, analyzing and relating as much relevant data as possible to the market prices of common stocks-past, present, and prospective. Professor Benston's underlying premise that published accounting reports are used by investors to evaluate their expectations of the corporation seems unarguable. The financial history and prospects of a corporation expressed in figures extracted from standard accounting statements are the beginning and end of every professional investment analysis and every professional investment decision. The interpretation of these figures and the relative importance attached to one or another differ but, in my experience, the accounting data language in which investor problems are stated and decisions reached is universal. Second, the premise that changes in investors' expectations caused by published accounting data should be reflected in a change in the price of a corporation's stock seems equally valid. It is the how and especially the when of this cause-effect relationship that is difficult to isolate. In my opinion, it is very complex and veritably defies reduction to any usable mathematical equation. In the beginning, Professor Benston notes that an investor confronted with a change in his expectations has the alternative of buying or selling the security in question. Yes, but when? We have all heard of investors who place orders at once upon reading or hearing a piece of information that affects his expectations. Conversely, many investment decisions are reached only after passage through an elaborate committee procedure involving a lapse of considerable time. Thus, even